2017
DOI: 10.1186/s11671-017-2199-1
|View full text |Cite
|
Sign up to set email alerts
|

Heating-Enhanced Dielectrophoresis for Aligned Single-Walled Carbon Nanotube Film of Ultrahigh Density

Abstract: In this paper, we demonstrate that the alignment density of individualized single-walled carbon nanotubes (SWCNTs) can be greatly improved by heating-enhanced dielectrophoresis (HE-DEP) process. The observations by scanning electron microscope (SEM) suggest ultrahigh alignment density and good alignment quality of SWCNTs. The intuitive alignment density of individualized SWCNTs is much higher than the currently reported best results. The reason of this HE-DEP process is explained by simulation work and ascribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Increasing SWNT concentration further led to a linear density increase, which inevitably causes the formation of a second and possibly third layer. An alternate approach for enhancing SWNT density was proposed by Gu et al, 262 who reported the fabrication of horizontal SWNT films using a heating enhanced DEP process, where the "convection force" induced by the heating effect promotes the exchange and transfer of individual SWNTs to the vicinity of the DEP grooves. The prepared horizontal SWNTs with ultrahigh density will have important implications in the fabrication of high-quality nanodevices if the degree of alignment can be further improved.…”
Section: Dielectrophoresismentioning
confidence: 99%
“…Increasing SWNT concentration further led to a linear density increase, which inevitably causes the formation of a second and possibly third layer. An alternate approach for enhancing SWNT density was proposed by Gu et al, 262 who reported the fabrication of horizontal SWNT films using a heating enhanced DEP process, where the "convection force" induced by the heating effect promotes the exchange and transfer of individual SWNTs to the vicinity of the DEP grooves. The prepared horizontal SWNTs with ultrahigh density will have important implications in the fabrication of high-quality nanodevices if the degree of alignment can be further improved.…”
Section: Dielectrophoresismentioning
confidence: 99%
“…The method is called light-assisted DEP (L-DEP) and was applied to sc-SWCNT since their relative permittivity is lower than mt-SWCNT [205]. Optically-induced dielectrophoresis (O-DEP) [297], heating-enhanced DEP (HE-DEP) [298], and chemically-enhanced DEP are other non-conventional DEP use other forces to assist the alignment process. In O-DEP, an optical source was used to illuminate sites on a photoconductive layer to generate a nonuniform electric field at the assembly location.…”
Section: Discussionmentioning
confidence: 99%
“…The density of the array obviously increases with the duration time, just as summarized in figure 5(e). When chosen the duration time of 30 min, the density of aligned sc-SWCNTs array reaches up to 54±2 tubes μm −1 which is the highest linear density by dielectrophoresis method among relevant reports as shown in table 1 [24,26,41,42]. Transfer curves of sc-SWCNT FETs with different array densities are shown in figure 6(a).…”
Section: Optimization Of Linear Density With Duration Timementioning
confidence: 95%
“…Although off currents increase with the increase of array density, the on/off current ratios have no obvious correlation with the density, keeping at around 10 4 as seen in figure 6(b). Table 1 shows the related reports on the electrical properties of SWCNT transistors in dielectrophoresis method [24,26,41,42]. The transistor fabricated in this work exhibits obvious advantages in on/off current ratio under short channel due to high purity of sc-SWCNT and appropriate ratio between tube length and channel length.…”
Section: Optimization Of Linear Density With Duration Timementioning
confidence: 99%